2023
DOI: 10.1371/journal.pgph.0001496
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health promotion: A systematic review involving effectiveness of faith-based institutions in facilitating maintenance of normal blood pressure

Abstract: Globally, faith institutions have a range of beneficial social utility, but a lack of understanding remains regarding their role in cardiovascular health promotion, particularly for hypertension. Our objective was assessment of modalities, mechanisms and effectiveness of hypertension health promotion and education delivered through faith institutions. A result-based convergent mixed methods review was conducted with 24 databases including MEDLINE, Embase and grey literature sources searched on 30 March 2021, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…[41] The potential integration of religious and cultural considerations into health promotion programs could be instrumental in enhancing their efficacy. [42] Utilizing community venues like mosques for health education could substantially improve outreach and engagement. [43] In summary, this study illustrates the complex interactions between sociodemographic factors, lifestyle behaviors, and weight changes during Ramadan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] The potential integration of religious and cultural considerations into health promotion programs could be instrumental in enhancing their efficacy. [42] Utilizing community venues like mosques for health education could substantially improve outreach and engagement. [43] In summary, this study illustrates the complex interactions between sociodemographic factors, lifestyle behaviors, and weight changes during Ramadan.…”
Section: Discussionmentioning
confidence: 99%
“…The potential integration of religious and cultural considerations into health promotion programs could be instrumental in enhancing their efficacy. [42] Utilizing community venues like mosques for health education could substantially improve outreach and engagement. [43]…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have shown positive effects of faith-based interventions to promote health and wellness among vulnerable communities. For example, Sanusi et al ( PLOS Global Public Health , 2023) concluded that “in addressing the global hypertension epidemic, cardiovascular health promotion roles of faith institutions probably hold unrealised potential in research and utility as viable assets or adjuncts to healthcare systems, crucially in low-income, religious or underserved communities” [ 15 ]. The moral status of places of worship within communities enhances acceptability of community-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that churches can play an important role in promoting wellness (Campbell et al, 2007;Gross et al, 2018). They may provide programs to reduce the risk of obesity and to help those living with diabetes and high blood pressure (Berkley-Patton et al, 2020;Brewer et al, 2020;Sanusi et al, 2023). Although Frenk and Trinitapoli (2013) found that only slightly more than 5% of US churches offer programs for people living with HIV, many provide support and resources for church and community members at greater risk for HIV.…”
Section: Introductionmentioning
confidence: 99%